RANCANGAN MONITORING PROTEKSI TEMPERATURE PADA DETECTION GAS PRESURE TEMPERATURE (DGPT) TRANSFORMATOR DI BANDAR UDARA INTERNASIONAL SOEKARNO-HATTA - Bachrul Huda; Yenni Arnas; Rafy Fauzian Agsal (Politeknik Penerbangan Indonesia Curug, 2016)
Soekarno – Hatta International Airport is one of the airport under PT. Angkasa Pura II, which provides services in transport sector. One of the support to actualize flight service that is safe and comfortable is the existence of infrastructure and facilities in that airport. Especially electric facilities at the airport should be maintained on the system back up or supply from PLN. One of the tools that support the supply system is a transformer that serves to lower the voltage of PLN is 20 KV to 380 V in step down system. The transformer at Soekarno – Hatta International Airport has 83 units spread across each sub station. To maintain optimum transformer, it necessary to care the transformer in each transformer sub station especially the temperature of transformer should always be monitored to prevent over temperature which can result in transformer windings as well as components to be damaged and the unoptimal operation. To check the temperature of the transformer in each sub station requires effort and time that far away from the sub station control room as well as through the bottleneck is an obstacles to check the temperature of the transformer in each sub station